2009
DOI: 10.1038/nature08290
|View full text |Cite
|
Sign up to set email alerts
|

The Ink4/Arf locus is a barrier for iPS cell reprogramming

Abstract: The mechanisms involved in the reprogramming of differentiated cells into induced Pluripotent Stem (iPS) cells by Oct4, Klf4 and Sox2 (3F) remain poorly understood 1 . The Ink4/Arf tumour suppressor locus encodes three potent inhibitors of proliferation, namely p16 Ink4a , p15 Ink4b and Arf, which are basally expressed in differentiated cells and upregulated by aberrant mitogenic signals 2-4 . We show here that the locus is completely silenced in iPS cells, as well as in embryonic stem (ES) cells, acquiring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
734
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 885 publications
(786 citation statements)
references
References 30 publications
46
734
2
4
Order By: Relevance
“…3A) as reported in earlier findings (Li et al ., 2009; Kim et al ., 2010; Cheng et al ., 2011; Wang et al ., 2011; Rohani et al ., 2014). We reprogrammed SkMs from both young and old mice using classic Yamanaka factors, and colonies were stained with alkaline phosphatase (ALP) on day 16–18 and counted to assess reprogramming efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3A) as reported in earlier findings (Li et al ., 2009; Kim et al ., 2010; Cheng et al ., 2011; Wang et al ., 2011; Rohani et al ., 2014). We reprogrammed SkMs from both young and old mice using classic Yamanaka factors, and colonies were stained with alkaline phosphatase (ALP) on day 16–18 and counted to assess reprogramming efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that older and senescent cells are more resistant to reprogramming (Li et al ., 2009; Kim et al ., 2010; Cheng et al ., 2011; Wang et al ., 2011; Rohani et al ., 2014). These observations have established the importance of current efforts underway to understand the biology of cell reprogramming in the context of chronological and replicative age.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations